2018
DOI: 10.1186/s13068-018-1248-z
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of corn stover slurries during fermentation by Clostridium thermocellum

Abstract: BackgroundMilling during fermentation, termed cotreatment, has recently been proposed as an alternative to thermochemical pretreatment as a means to increase the accessibility of lignocellulosic biomass to biological attack. A central premise of this approach is that partial solubilization of biomass changes the slurry’s physical properties such that milling becomes more impactful and more feasible. A key uncertainty is the energy required to mill partially fermented biomass. To inform both of these issues, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The apparent viscosity decreased as the hydrolysis process progressed. The decrease of viscosity could be explained by the decreased insoluble solid content and the modified particle properties as hydrolysis progressed [18,19]. The viscosity during EH was used to estimate the energy consumption for mixing according to the theory in "Methods" section, and this is discussed in the next section.…”
Section: Rheological Behavior Of Bmcs Slurries: Apparent Viscosity and Yield Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…The apparent viscosity decreased as the hydrolysis process progressed. The decrease of viscosity could be explained by the decreased insoluble solid content and the modified particle properties as hydrolysis progressed [18,19]. The viscosity during EH was used to estimate the energy consumption for mixing according to the theory in "Methods" section, and this is discussed in the next section.…”
Section: Rheological Behavior Of Bmcs Slurries: Apparent Viscosity and Yield Stressmentioning
confidence: 99%
“…The effects of solid loading, composition and particle morphology (including particle size, size distribution and aspect ratio) on the rheological properties of the biomass slurries have been reported [12][13][14][15][16]. Studies have also looked at the evolution of the rheological behavior during the course of saccharification or fermentation [17][18][19]. In general, biomass slurries containing smaller particles exhibit lower viscosity and yield stress under same solids loading [14,15,20], which implies that reducing particle size may potentially improve the rheology of high-solids slurry and therefore reduce the energy consumption for mixing.…”
Section: Introductionmentioning
confidence: 99%
“…For laminar flow, relevant for high-solids lignocellulose slurries, the mass transfer coefficient is proportional to the viscosity to the À0.5 power. Because the viscosity of biomass slurries at high solids is in general markedly higher than that of water, 70 the mass transfer coefficients for such slurries are typically much lower than that for water. Aeration provides an illustrative example of the impact of slurries on processing costs.…”
Section: View Article Onlinementioning
confidence: 99%
“…[148][149][150][151] However, the profound physical changes that accompany biologically-mediated plant cell wall polysaccharide deconstruction may enable much-reduced energy requirements for milling at an intensity sufficient to enhance solubilization. [68][69][70] In experiments involving fermentation without milling and milling without fermentation followed by a second fermentation, Paye et al 136 found that ball milling for five minutes nearly doubled solubilization of senescent switchgrass by C. thermocellum compared to two fermentations without milling. Balch et al 62 found a similar enhancement of senescent switchgrass solubilization for C. thermocellum fermentation with continuous ball milling as compared to an unmilled control.…”
Section: Energy and Environmental Science Reviewmentioning
confidence: 99%
See 1 more Smart Citation